2009
DOI: 10.1073/pnas.0912658106
|View full text |Cite
|
Sign up to set email alerts
|

The γ isoform of CaM kinase II controls mouse egg activation by regulating cell cycle resumption

Abstract: Fertilization triggers a rise in intracellular Ca 2+ concentration ([Ca 2+ ] i ) in the egg that initiates a series of events known as egg activation. These events include cortical granule exocytosis that establishes a block to polyspermy, resumption of meiosis, and recruitment of maternal mRNAs into polysomes for translation. Several calcium-dependent proteins, including calcium/calmodulin-dependent protein kinase II (CaMKII), have been implicated in egg activation. However, the precise role of CaMKII in med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 42 publications
3
110
0
Order By: Relevance
“…The role of CaMKII on mammalian egg activation was convincingly shown by studies in the mouse, in which expression of constitutive active forms of CaMKII into eggs initiated all events of egg activation, except CG exocytosis, and promoted development to the blastocyst stage (Madgwick et al 2005;Knott et al 2006). Conversely, depletion of the CaMKIIg isoform abrogated the ability of these eggs to exit MII in response to [Ca 2þ ] i stimulation (Backs et al 2010;Chang et al 2009), causing infertility. Research also implicated Emi2 in MII arrest in the mouse, as inhibition of Emi2 synthesis prevents cyclin B1 accumulation during maturation , which causes spontaneous activation (Shoji et al 2006).…”
Section: Events Of Egg Activation Require [Ca 2þ ] I Increasesmentioning
confidence: 95%
See 2 more Smart Citations
“…The role of CaMKII on mammalian egg activation was convincingly shown by studies in the mouse, in which expression of constitutive active forms of CaMKII into eggs initiated all events of egg activation, except CG exocytosis, and promoted development to the blastocyst stage (Madgwick et al 2005;Knott et al 2006). Conversely, depletion of the CaMKIIg isoform abrogated the ability of these eggs to exit MII in response to [Ca 2þ ] i stimulation (Backs et al 2010;Chang et al 2009), causing infertility. Research also implicated Emi2 in MII arrest in the mouse, as inhibition of Emi2 synthesis prevents cyclin B1 accumulation during maturation , which causes spontaneous activation (Shoji et al 2006).…”
Section: Events Of Egg Activation Require [Ca 2þ ] I Increasesmentioning
confidence: 95%
“…Importantly, the widespread expression of PKC isoforms in oocytes (Gallicano et al 1997;Eliyahu et al 2001;Page Baluch et al 2004), along with their distinct cellular distribution (Viveiros et al 2001;Page Baluch et al 2004), and the implications of their impact on Ca 2þ influx (Halet 2004), suggest important roles for these enzymes in setting off embryo development. CaMKII was also expected to participate in CG exocytosis, although the aforementioned studies using constitutively active forms of the protein (Knott et al 2006) or eggs devoid of CaMKII have ruled out this possibility (Backs et al 2010;Chang et al 2009). Recent studies have implicated myosin light chain kinase (MLCK), another Ca 2þ -dependent kinase, as being involved in CG exocytosis in mouse fertilization, as pharmacological inhibitors greatly diminished their release in response to Ca 2þ stimulation (Matson et al 2006).…”
Section: Events Of Egg Activation Require [Ca 2þ ] I Increasesmentioning
confidence: 99%
See 1 more Smart Citation
“…S28 is included in the common region, while T37 and S38 are involved in an alternative splicing region of the enzyme. It is known in mouse eggs that calcium/calmodulin-dependent protein kinase II gamma is activated by calcium/calmodulin through autophosphorylation at T287 and controls egg activation by regulating cell cycle resumption (38). Phosphorylation at T37 or S38 of the enzyme in Xenopus eggs may be involved in the egg activation in an isoform-specific manner, though these are different from the earlier autophosphorylation residues.…”
Section: Validation Of Phosphorylation Sitesmentioning
confidence: 99%
“…Both PKC and CaMKII have several different isotypes, and the different isotypes have different substrate specifities. The subunit of CaMKII was shown to be effective in the resumption of mouse eggs (Johnson et al, 1998), while others have shown cell cycle resumption to be dependent on the subunit (Change et al, 2009;Backs et al, 2010). A plausible alternative explanation is upon injection the constitutively active CaMKII (Knott et al, 2006) could immediately phosphorylate substrates in the cytoplasm and alter the sequence of events leading to activation.…”
Section: Fertilizationmentioning
confidence: 99%